Preparation method of Ru-coated Ni2P-Ni3P core-shell structure catalyst, PEM membrane electrode and preparation method of PEM membrane electrode

By using Ru@Ni2P-Ni3P core-shell structure catalyst in PEM electrolytic hydrogen production system, the problem of high cost of precious metal catalysts is solved, and the effect of reducing the use of precious metals and improving catalytic activity is achieved, which significantly reduces the operation of PEM electrolytic cell. Cost and power consumption.

CN119307962APending Publication Date: 2025-01-14TIANJI EQUIPMENT TECHNOLOGY (SUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411239566.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The precious metal catalysts used in existing PEM electrolytic hydrogen production systems are expensive, which limits their large-scale market-oriented applications. In particular, the use and cost of IrO2 anode catalysts are difficult to reduce, and the global reserves of Ir are scarce.

Method used

Ru@Ni2P-Ni3P core-shell structure catalyst was used to prepare Ru@Ni2P-Ni3P core-shell nanoparticles with high catalytic activity by using Ru@Ni2P-Ni3P as the core by using Ru@Ni2P-Ni3P as the core by using Ru@Ni2P-Ni3P core-shell nanoparticles with high catalytic activity by specific heat treatment and synthesis methods. , as an alternative catalyst, reduce the amount of precious metals used and improve the catalytic performance.

Benefits of technology

有效降低了贵金属的使用量和成本,同时提高了催化剂的催化活性和电流密度,降低了电耗,显著降低了PEM电解槽的运行成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307962A_ABST
    Figure CN119307962A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Ru-coated Ni2P-Ni3P core-shell structure catalyst, a PEM membrane electrode and a preparation method of the PEM membrane electrode. The preparation method of the catalyst comprises the following steps: (1) adding a nickel precursor into a first solvent, adding a phosphorus source, mixing, heating, raising the temperature to a first temperature, maintaining the temperature for a certain period of time, raising the temperature to a second temperature, maintaining the temperature for a certain period of time, and carrying out a reaction process in a protective atmosphere; (2) adding the ruthenium precursor into a second solvent, adding a third solvent at the same time, and heating and stirring to dissolve the ruthenium precursor; (2) adding the mixed solution obtained in the step (1) into the solution obtained in the step (2), raising the temperature to a third temperature, maintaining the temperature for a plurality of time, raising the temperature to a fourth temperature, maintaining the temperature for a plurality of time, and carrying out a reaction process in a protective atmosphere; and after the reaction is finished, cleaning and loading by using a carrier. According to the invention, Ru is used as a shell of nanoparticles, so that the usage amount of noble metal can be greatly reduced, and the cost of a PEM electrolytic cell is reduced; cheap transition metal phosphide is used as a core, so that the cost of the catalyst is further reduced, the overall catalytic performance of the catalyst is improved, the current density of a PEM electrolytic bath is improved, and the power consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a catalyst, a membrane electrode and a method for preparing the same, and in particular to a method for preparing a Ru@Ni2P-Ni3P core-shell structure catalyst, a PEM membrane electrode and a method for preparing the same. Background Art

[0002] The PEM water electrolysis hydrogen production system has been rapidly developed in recent years due to its advantages such as adaptability to fluctuating power, fast startup speed, high current density, and small size. Unfortunately, the PEM cathode and anode catalysts currently use expensive precious metal catalysts, which account for 10% of the total electrolyzer cost, limiting its large-scale market application.

[0003] Reducing the amount of precious metals used in PEM electrolyzers is the key to reducing costs. Currently, the most mature PEM anode catalyst is the precious metal oxide IrO2, and the amount used is usually 4 mg / cm 2 . However, the global reserves of precious metal Ir are extremely small, and its price is higher than other precious metals (Pt, Ru, Pd, etc.), so reducing the use of precious metal Ir or replacing Ir with other relatively cheap precious metals has become the direction of current technological development. Precious metals Ru and Ir have similar properties, both have 7 electrons in the d orbital, have suitable adsorption energy for oxygen-containing intermediates, and are the most active metals in acidic water electrolysis oxygen evolution (OER). At the same time, Ru has more abundant earth reserves than Ir, and the price of Ru is only 1 / 6 of Ir. Therefore, using Ru to replace Ir as a PEM anode catalyst is a potential technological development direction. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a Ru@Ni2P-Ni3P core-shell structure catalyst which can reduce the amount of precious metals used and has good catalytic performance;

[0005] The second object of the present invention is to provide a PEM membrane electrode with good catalytic performance;

[0006] The third object of the present invention is to provide the above-mentioned PEM membrane electrode preparation method.

[0007] Technical solution: The preparation method of the Ru@Ni2P-Ni3P core-shell structure PEM anode catalyst of the present invention comprises the following steps:

[0008] (1) adding a nickel precursor to a first solvent, then adding a phosphorus source, mixing, and heating, first raising the temperature to a first temperature and maintaining it for a certain time, and then raising the temperature to a second temperature and maintaining it for a certain time, and the reaction process is carried out under a protective atmosphere;

[0009] (2) adding a ruthenium precursor to the second solvent and simultaneously adding a third solvent, heating and stirring to dissolve the ruthenium precursor;

[0010] (3) adding the mixed solution obtained in step (1) to the solution in step (2), first raising the temperature to the third temperature and maintaining it for a certain time, and then raising the temperature to the fourth temperature and maintaining it for a certain time, and the reaction process is carried out under a protective atmosphere;

[0011] (4) After the reaction is completed, the mixture is cleaned and loaded with a carrier.

[0012] Preferably, the nickel precursor in step (1) comprises one or a combination of any two of nickel chloride, nickel acetate, nickel sulfate, and nickel acetylacetonate; the certain molar amount of the nickel precursor in step (1) has a molar amount range of 0-1mmol, for example, it can be 0.1mmol, 0.2mmol, 0.3mmol, 0.4mmol, 0.5mmol, 0.6mmol, 0.7mmol, 0.8mmol, 0.9mmol, 1.0mmol.

[0013] Preferably, the first solvent in step (1) comprises one or more combinations of oleylamine, dodecylamine, octadecylamine and trivinylamine.

[0014] Preferably, the amount of the first solvent in step (1) is 5-30 mL, for example, 5 mL, 10 mL, 15 mL, 20 mL, 25 mL, or 30 mL.

[0015] Preferably, the phosphorus source in step (1) comprises one or more combinations of sodium hypophosphite, potassium dihydrogen phosphate, tri-n-octyl phosphine, phosphate ester, and ATP.

[0016] Preferably, in step (1), the first temperature range is 10-150°C, which may be 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, including but not limited to the listed heating temperatures. The heating time is 1-30 min, for example, 1 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min.

[0017] Preferably, in step (1), the second temperature range is 280-320°C, and can be 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, including but not limited to the listed heating temperatures. The heating time is 30-200 min, for example, 30 min, 60 min, 90 min, 120 min, 150 min, 180 min, 200 min.

[0018] Preferably, the stirring rate in step (1) is 10-2000 rpm, for example, it can be 10 rpm, 100 rpm, 300 rpm, 500 rpm, 700 rpm, 900 rpm, 1100 rpm, 1300 rpm, 1500 rpm, 1700 rpm, or 2000 rpm.

[0019] Preferably, in step (1), the protective atmosphere is mainly an inert gas, including one or a combination of nitrogen, argon and helium.

[0020] Preferably, in step (1), after adding the phosphorus source, ultrasonic mixing and dispersion are performed, and the ultrasonic power is 10-40 Hz, which can be 10 Hz, 15 Hz, 20 Hz, 25 Hz, 30 Hz, 35 Hz, 40 Hz, including but not limited to the listed ultrasonic powers. The ultrasonic time is 1-60 min, which can be 1 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min.

[0021] Preferably, the ruthenium precursor in step (2) includes one or a combination of ruthenium acetylacetonate, ruthenium chloride, ruthenium acetate, bis(pentamethylcyclopentene)ruthenium, and bis(pentamethylcyclopentene)ruthenium. The molar amount of the ruthenium precursor is 0-0.1mmol, for example, 0.01mmol, 0.02mmol, 0.03mmol, 0.04mmol, 0.05mmol, 0.06mmol, 0.07mmol, 0.08mmol, 0.09mmol, 0.1mmol. The molar ratio of the ruthenium precursor to the nickel precursor is 1:1-1:15.

[0022] Preferably, the second solvent in step (2) comprises one or a combination of n-hexane, cyclohexane, octadecene, oleic acid, p-phenylene ether, and dimethyl sulfoxide. The amount of the second solvent added is 1-20 mL, for example, 1 mL, 5 mL, 10 mL, 15 mL, or 20 mL.

[0023] Preferably, the third solvent in step (2) comprises one or more combinations of oleylamine, dodecylamine, octadecylamine, and trivinylamine. The amount of the third solvent added is 1-10 mL, for example, 1 mL, 2 mL, 4 mL, 6 mL, 8 mL, and 10 mL. The volume ratio of the second solvent to the third solvent is 8:1-1:1.

[0024] Preferably, the temperature range described in step (2) is 10-150°C, for example, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C. The heating time is 1-30min, for example, 1min, 5min, 10min, 15min, 20min, 25min, 30min, including but not limited to the listed heating times. The stirring rate is 10-1000rpm, for example, 10rpm, 100rpm, 300rpm, 500rpm, 700rpm, 900rpm, 1100rpm.

[0025] Preferably, the third temperature in step (3) is in the range of 10-150°C, for example, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, including but not limited to the listed heating temperatures. The heating time is 1-30 min, for example, 1 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min.

[0026] Preferably, the fourth temperature in step (3) is in the range of 260-320°C, for example, 10°C, 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, 320°C, including but not limited to the listed heating temperatures. The heating time is 10-300 min, for example, 10 min, 50 min, 100 min, 150 min, 200 min, 250 min, 300 min.

[0027] Preferably, in step (3), the reaction process is carried out under stirring; the stirring rate is 10-2000rpm, for example, it can be 10rpm, 100rpm, 300rpm, 500rpm, 700rpm, 900rpm, 1100rpm, 1300rpm, 1500rpm, 1700rpm, 2000rpm.

[0028] Preferably, the protective atmosphere in step (3) is mainly an inert gas, including one or a combination of nitrogen, argon and helium.

[0029] Preferably, in step (4), a certain amount of solvent and detergent are used for cleaning; the solvent includes one or more combinations of n-hexane, hexane, cyclohexane, n-butane, and acetone; the detergent includes one or more combinations of ethanol, methanol, isopropanol, and ether.

[0030] Preferably, in step (4), the carrier includes at least one of activated carbon, carbon cloth, graphene, and carbon nanotubes.

[0031] The PEM membrane electrode described in the present invention, the catalyst in the PEM membrane electrode is the Ru@Ni2P-Ni3P core-shell structure catalyst prepared by the above method.

[0032] The slurry for preparing the PEM membrane electrode includes Ru@Ni2P-Ni3P core-shell nanoparticles, proton exchange membrane ionomer, isopropanol and water. Based on the mass of Ru@Ni2P-Ni3P core-shell nanoparticles as 100%, the content of the proton exchange membrane ionomer is 5%-20%, for example, 5%, 10%, 15%, 20%. The ratio of isopropanol to water is 10 / 1-1 / 1, for example, 10 / 1, 9 / 1, 8 / 1, 7 / 1, 6 / 1, 5 / 1, 4 / 1, 3 / 1, 2 / 1, 1 / 1.

[0033] The cathode catalyst in the PEM electrolyzer is commercial 40% Pt / C, and the composition of the cathode catalyst slurry is the same as that of the anode catalyst slurry.

[0034] After the catalyst slurry is prepared, the catalyst needs to be fully dispersed to ensure that it does not settle within 48 hours. To achieve this goal, the present invention adopts ultrasonic vibration plus mechanical stirring.

[0035] Preferably, the power of ultrasonic oscillation is 10-100Hz, for example, it can be 10Hz, 20Hz, 30Hz, 40Hz, 50Hz, 60Hz, 70Hz, 80Hz, 90Hz, 100Hz. The ultrasonic time is 1-200min, for example, it can be 10min, 30min, 50min, 70min, 90min, 110min, 130min, 150min, 170min, 200min. The speed of mechanical stirring is 10-1000rpm, for example, it can be 10rpm, 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm. The stirring time is 1-200 min, for example, 10 min, 30 min, 50 min, 70 min, 90 min, 110 min, 130 min, 150 min, 170 min, or 200 min.

[0036] The evenly dispersed catalyst slurry is ultrasonically sprayed. The anode catalyst slurry is sprayed onto the titanium felt, and the cathode catalyst slurry is sprayed onto the carbon cloth. The size of the carbon cloth and the titanium felt are both 2*2cm.

[0037] Preferably, the anode catalyst loading is 1-4 mg / cm 2, for example, 1 mg / cm 2 , 2mg / cm 2 、3mg / cm 2 , 4mg / cm 2 ; The cathode catalyst loading is 0.5-2 mg / cm 2 , for example, 0.5 mg / cm 2 , 1mg / cm 2 , 1.5mg / cm 2 , 2mg / cm 2 .

[0038] The above-mentioned method for preparing the PEM membrane electrode is to form the proton exchange membrane, the catalyst layer and the gas diffusion layer by hot pressing; the temperature during the hot pressing is 10-150° C. and the pressure is 1-5 MPa.

[0039] Preferably, the proton exchange membrane is Nafion115; the temperature during hot pressing can be 10°C, 50°C, 100°C, or 150°C; and the pressure during hot pressing can be 1MPa, 2MPa, 3MPa, 4MPa, or 5MPa.

[0040] Principle of the invention: The present invention proposes a method for preparing a core-shell nanomaterial with a precious metal Ru as a shell and a transition metal phosphide Ni2P-Ni3P mixed phase as a core. On the one hand, the use of cheap Ru instead of Ir can reduce the cost of the PEM electrolyzer, and the use of Ru as a catalyst shell can be further reduced. At the same time, the use of cheap transition metal phosphides Ni2P-Ni3P as a core can further reduce the cost of PEM. On the other hand, the electronic interaction between Ni2P-Ni3P and Ru can not only enhance the stability of Ru in acidic OER, but also improve the overall catalytic activity of the Ru@Ni2P-Ni3P core-shell catalyst. In summary, the Ru@Ni2P-Ni3P core-shell catalyst prepared in the present invention can not only significantly reduce the use of precious metals, but also enhance the catalytic activity of the catalyst.

[0041] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:

[0042] (1) Using Ru, which is relatively cheaper than Ir, as the shell of the nanoparticles can significantly reduce the amount of precious metals used, thereby reducing the cost of the PEM electrolyzer;

[0043] (2) Using cheap transition metal phosphides as the core can further reduce the catalyst cost, and the electronic interaction between transition metal phosphides and precious metals can improve the overall catalytic performance of the core-shell structure catalyst, increase the current density of the PEM electrolyzer, and reduce power consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The polarization curve of PEM water electrolysis provided in Example 1;

[0045] Figure 2 This is a PEM water electrolysis stability test diagram provided in Example 1. DETAILED DESCRIPTION

[0046] The present invention is described in further detail below.

[0047] Example 1

[0048] This embodiment provides a method for preparing Ru@Ni2P-Ni3P core-shell nanoparticles, and the specific steps are as follows:

[0049] (1) 0.1 mmol of nickel acetylacetonate was added to 15 mL of dodecylamine, and then 1.2 mL of tri-n-octylphosphine was added.

[0050] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 300°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0051] (3) 0.01 mmol of ruthenium chloride was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0052] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130° C. and heated for 30 min, and then the temperature is raised to 280° C. and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0053] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0054] The Ru@Ni2P-Ni3P core-shell nanoparticles prepared in this embodiment are first characterized by crystal structure using an X-ray diffractometer (XRD). In the obtained X-ray diffraction spectrum, the peak positions at 40.8°, 44.6°, 47.3°, 54.2° and 54.9° correspond to the (111), (201), (210), (300) and (211) crystal planes of hexagonal Ni2P, respectively. In addition, the peak positions at 41.8°, 46.6°, 43.6°, 45.2° and 52.7° correspond to the (231), (141), (112), (240) and (132) crystal planes of tetragonal Ni3P, respectively. From the XRD results, it can be seen that the nanoparticle core is composed of mixed phase phosphide Ni2P and Ni3P. The XRD spectrum does not have a peak of Ru, because Ru, as the shell of the nanoparticle, has a very small content itself and is not easy to peak.

[0055] Next, spherical aberration-corrected transmission electron microscopy (HADDF-HRTEM) was used to characterize the core-shell nanoparticles. Spherical aberration electron microscopy showed that the average diameter of the nanoparticles was 8.2nm, and they were uniformly spherical. HRTEM images showed that Ru was mainly distributed on the periphery of the nanoparticles, with a thickness of 3 atomic layers. The elemental scanning distribution map showed that Ru was mainly in the outer layer, and the inner core was nickel phosphide.

[0056] Combining XRD and HADDF-HRTEM, it can be determined that Ru@Ni2P-Ni3P core-shell nanoparticles were successfully prepared in this example.

[0057] Example 2

[0058] (1) 0.1 mmol of nickel acetylacetonate was added to 15 mL of dodecylamine, and then 1.2 mL of tri-n-octylphosphine was added.

[0059] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 300°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0060] (3) 0.02 mmol of ruthenium chloride was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0061] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130° C. and heated for 30 min, and then the temperature is raised to 280° C. and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0062] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0063] Example 3

[0064] (1) 0.1 mmol of nickel acetylacetonate was added to 15 mL of dodecylamine, and then 1.2 mL of tri-n-octylphosphine was added.

[0065] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 300°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0066] (3) 0.03 mmol of ruthenium chloride was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0067] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130° C. and heated for 30 min, and then the temperature is raised to 280° C. and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0068] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0069] The Ru and Ni element contents of Examples 1-3 were accurately measured using inductively coupled plasma optical emission spectroscopy (ICP-OES). The results are shown in Table 1:

[0070] Table 1

[0071] sample Ni / Ru molar ratio Ru mass fraction / % Example 1 13.5:1 8.32 Example 2 8.2:1 12.73 Example 3 5.3:1 18.14

[0072] Example 4

[0073] (1) 0.1 mmol of nickel acetylacetonate was added to 15 mL of dodecylamine, and then 1.2 mL of tri-n-octylphosphine was added.

[0074] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 320°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0075] (3) 0.01 mmol of ruthenium chloride was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0076] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130° C. and heated for 30 min, and then the temperature is raised to 280° C. and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0077] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0078] Example 5

[0079] (1) 0.1 mmol of nickel acetylacetonate was added to 15 mL of dodecylamine, and then 1.2 mL of tri-n-octylphosphine was added.

[0080] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 300°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0081] (3) 0.01 mmol of ruthenium chloride was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0082] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130° C. and heated for 30 min, and then the temperature is raised to 260° C. and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0083] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0084] Example 6

[0085] (1) 0.1 mmol of nickel acetylacetonate was added to 15 mL of dodecylamine, and then 1.2 mL of tri-n-octylphosphine was added.

[0086] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 300°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0087] (3) 0.01 mmol of ruthenium chloride was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0088] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130° C. and heated for 30 min, and then the temperature is raised to 300° C. and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0089] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0090] Example 7

[0091] The present invention also provides a method for preparing a PEM membrane electrode, and the preparation process is as follows:

[0092] The anode catalyst loading was 2 mg / cm 2Weigh the above Ru@Ni2P-Ni3P core-shell nanoparticles, add 15% proton exchange membrane ionomer by mass, add isopropanol and water in a ratio of 10 / 1, and keep the volume of the whole slurry at 20mL. After the anode catalyst slurry is prepared, first ultrasonicate it at 80Hz ultrasonic power for 120min, then mechanically stir it at 1000rpm for 60min, and finally spray the evenly dispersed slurry onto 2*2cm 2 on titanium felt.

[0093] The cathode catalyst loading was 1 mg / cm 2 Weigh a commercial 40% Pt / C catalyst, a 15% proton exchange membrane ionomer, and add isopropanol and water in a ratio of 10 / 1. The volume of the entire slurry is maintained at 20 mL. After the cathode catalyst slurry is prepared, it is first ultrasonicated at 80 Hz for 120 min, then mechanically stirred at 1000 rpm for 60 min, and finally the evenly dispersed slurry is sprayed onto a 2*2 cm 2 on the carbon cloth.

[0094] Membrane electrode preparation: The carbon cloth and titanium felt sprayed with the catalyst were pressed onto both sides of the Nafion 115 proton exchange membrane by hot pressing. The hot pressing pressure was 3 MPa, the hot pressing temperature was 120°C, and the hot pressing time was 1 min.

[0095] Finally, the prepared membrane electrode, current collecting plate, and bipolar plate were assembled into a single-chamber PEM electrolyzer, and the polarization curve and long-term durability of the PEM electrolyzer were tested at 60°C.

[0096] Example 8

[0097] The anode catalyst loading was 4 mg / cm 2 Weigh the above Ru@Ni2P-Ni3P core-shell nanoparticles, add 15% proton exchange membrane ionomer by mass, add isopropanol and water in a ratio of 10 / 1, and keep the volume of the whole slurry at 20mL. After the anode catalyst slurry is prepared, first ultrasonicate it at 80Hz ultrasonic power for 120min, then mechanically stir it at 1000rpm for 60min, and finally spray the evenly dispersed slurry onto 2*2cm 2 on titanium felt.

[0098] The cathode catalyst loading was 1 mg / cm 2Weigh a commercial 40% Pt / C catalyst, a 15% proton exchange membrane ionomer, and add isopropanol and water in a ratio of 10 / 1. The volume of the entire slurry is maintained at 20 mL. After the cathode catalyst slurry is prepared, it is first ultrasonicated at 80 Hz for 120 min, then mechanically stirred at 1000 rpm for 60 min, and finally the evenly dispersed slurry is sprayed onto a 2*2 cm 2 on the carbon cloth.

[0099] Membrane electrode preparation: The carbon cloth and titanium felt sprayed with the catalyst were pressed onto both sides of the Nafion 115 proton exchange membrane by hot pressing. The hot pressing pressure was 3 MPa, the hot pressing temperature was 120°C, and the hot pressing time was 1 min.

[0100] Finally, the prepared membrane electrode, current collecting plate, and bipolar plate were assembled into a single-chamber PEM electrolyzer, and the polarization curve and long-term durability of the PEM electrolyzer were tested at 60°C.

[0101] Example 9

[0102] The anode catalyst loading was 2 mg / cm 2 Weigh the above Ru@Ni2P-Ni3P core-shell nanoparticles, add 15% proton exchange membrane ionomer by mass, add isopropanol and water in a ratio of 10 / 1, and keep the volume of the whole slurry at 20mL. After the anode catalyst slurry is prepared, first ultrasonicate it at 80Hz ultrasonic power for 120min, then mechanically stir it at 1000rpm for 60min, and finally spray the evenly dispersed slurry onto 2*2cm 2 on titanium felt.

[0103] The cathode catalyst loading was 1 mg / cm 2 Weigh a commercial 40% Pt / C catalyst, a 15% proton exchange membrane ionomer, and add isopropanol and water in a ratio of 10 / 1. The volume of the entire slurry is maintained at 20 mL. After the cathode catalyst slurry is prepared, it is first ultrasonicated at 80 Hz for 120 min, then mechanically stirred at 1000 rpm for 60 min, and finally the evenly dispersed slurry is sprayed onto a 2*2 cm 2 on the carbon cloth.

[0104] Membrane electrode preparation: The carbon cloth and titanium felt sprayed with the catalyst were pressed onto both sides of the Nafion 115 proton exchange membrane by hot pressing. The hot pressing pressure was 5 MPa, the hot pressing temperature was 120°C, and the hot pressing time was 1 min.

[0105] Finally, the prepared membrane electrode, current collecting plate, and bipolar plate were assembled into a single-chamber PEM electrolyzer, and the polarization curve and long-term durability of the PEM electrolyzer were tested at 60°C.

[0106] Example 10

[0107] The anode catalyst loading was 2 mg / cm 2 Weigh the above Ru@Ni2P-Ni3P core-shell nanoparticles, add 15% proton exchange membrane ionomer by mass, add isopropanol and water in a ratio of 10 / 1, and keep the volume of the whole slurry at 20mL. After the anode catalyst slurry is prepared, first ultrasonicate it at 80Hz ultrasonic power for 120min, then mechanically stir it at 1000rpm for 60min, and finally spray the evenly dispersed slurry onto 2*2cm 2 on titanium felt.

[0108] The cathode catalyst loading was 1 mg / cm 2 Weigh a commercial 40% Pt / C catalyst, a 15% proton exchange membrane ionomer, and add isopropanol and water in a ratio of 10 / 1. The volume of the entire slurry is maintained at 20 mL. After the cathode catalyst slurry is prepared, it is first ultrasonicated at 80 Hz for 120 min, then mechanically stirred at 1000 rpm for 60 min, and finally the evenly dispersed slurry is sprayed onto a 2*2 cm 2 on the carbon cloth.

[0109] Membrane electrode preparation: The carbon cloth and titanium felt sprayed with the catalyst were pressed onto both sides of the Nafion 115 proton exchange membrane by hot pressing. The hot pressing pressure was 3 MPa, the hot pressing temperature was 140°C, and the hot pressing time was 1 min.

[0110] Finally, the prepared membrane electrode, current collecting plate, and bipolar plate were assembled into a single-chamber PEM electrolyzer, and the polarization curve and long-term durability of the PEM electrolyzer were tested at 60°C.

[0111] Comparative Example 1

[0112] (1) 0.1 mmol of nickel acetylacetonate was added to 15 mL of dodecylamine, and then 1.2 mL of tri-n-octylphosphine was added.

[0113] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 280°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0114] (3) 0.01 mmol of ruthenium chloride was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0115] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130° C. and heated for 30 min, and then the temperature is raised to 280° C. and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0116] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0117] The nanoparticles prepared in this comparative example are first characterized by crystal structure using an X-ray diffractometer (XRD). In the obtained X-ray diffraction pattern, the peak positions at 40.8°, 44.6°, 47.3°, 54.2° and 54.9° correspond to the (111), (201), (210), (300) and (211) crystal planes of hexagonal Ni2P, respectively. The peak positions at 40.66° and 47.3° correspond to the (111) and (200) planes of face-centered cubic Ru. From the XRD results, it can be seen that the nanoparticles Ni2P and the precious metal Ru are composed.

[0118] TEM shows that the nanoparticles are composed of two types, one is Ni2P with a diameter of 10nm, and the other is Ru with a diameter of 4nm. The two grow independently of each other and do not form a core-shell structure, which means that core-shell nanoparticles cannot be generated at this temperature.

[0119] Comparative Example 2

[0120] (1) 0.1 mmol of nickel acetylacetonate was added to 15 mL of dodecylamine, and then 1.2 mL of tri-n-octylphosphine was added.

[0121] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 300°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0122] (3) 0.01 mmol of ruthenium chloride was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0123] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130°C and heated for 30 min, and then the temperature is raised to 250°C and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0124] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0125] The crystal structure was characterized by X-ray diffractometer (XRD). In the obtained X-ray diffraction pattern, the peak positions at 40.8°, 44.6°, 47.3°, 54.2° and 54.9° correspond to the (111), (201), (210), (300) and (211) crystal planes of hexagonal Ni2P, respectively. In addition, the peak positions at 41.8°, 46.6°, 43.6°, 45.2° and 52.7° correspond to the (231), (141), (112), (240) and (132) crystal planes of tetragonal Ni3P, respectively. From the XRD results, it can be seen that the nanoparticle core is composed of mixed phase phosphide Ni2P and Ni3P.

[0126] TEM shows that there is only one type of nanoparticles, and the element distribution map shows that the nanoparticles contain only Ni and P, but no Ru, indicating that Ru is not generated.

[0127] Comparative Example 3

[0128] (1) 0.1 mmol of nickel acetylacetonate was added to 10 mL of dodecylamine, and then 1.2 mL of tri-n-octylphosphine was added.

[0129] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 300°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0130] (3) 0.01 mmol of ruthenium chloride was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0131] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130° C. and heated for 30 min, and then the temperature is raised to 280° C. and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0132] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0133] The crystal structure was characterized by X-ray diffractometer (XRD). In the obtained X-ray diffraction pattern, the peak positions at 40.8°, 44.6°, 47.3°, 54.2° and 54.9° correspond to the (111), (201), (210), (300) and (211) crystal planes of hexagonal Ni2P, respectively, indicating that the nanoparticles are mainly Ni2P.

[0134] TEM showed that the synthesized nanoparticles were spherical nanoparticles with a diameter of about 10 nm, and the element distribution scan showed that the spherical nanoparticles did not contain Ru, indicating that core-shell nanoparticles could not be synthesized under this condition.

[0135] Comparative Example 4

[0136] (1) 0.1 mmol of nickel acetylacetonate was added to 15 mL of dodecylamine, and then 3 mL of tri-n-octylphosphine was added.

[0137] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 300°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0138] (3) 0.01 mmol of ruthenium chloride was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0139] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130° C. and heated for 30 min, and then the temperature is raised to 280° C. and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0140] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0141] The crystal structure was characterized by X-ray diffractometer (XRD). In the obtained X-ray diffraction pattern, the peak positions at 40.8°, 44.6°, 47.3°, 54.2° and 54.9° correspond to the (111), (201), (210), (300) and (211) crystal planes of hexagonal Ni2P, respectively, indicating that the nanoparticles are mainly Ni2P.

[0142] TEM showed that the synthesized nanoparticles were spherical nanoparticles with a diameter of about 12 nm. The element distribution scan showed that the spherical nanoparticles did not contain Ru, indicating that core-shell nanoparticles could not be synthesized under this condition.

[0143] Comparative Example 5

[0144] (1) 0.1 mmol of nickel acetylacetonate was added to 15 mL of dodecylamine, and then 1.2 mL of tri-n-octylphosphine was added.

[0145] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 300°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0146] (3) 0.01 mmol of ruthenium acetylacetonate was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0147] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130° C. and heated for 30 min, and then the temperature is raised to 280° C. and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0148] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0149] First, the crystal structure was characterized by X-ray diffractometer (XRD). In the obtained X-ray diffraction pattern, the peak positions at 40.8°, 44.6°, 47.3°, 54.2° and 54.9° correspond to the (111), (201), (210), (300) and (211) crystal planes of hexagonal Ni2P, respectively. In addition, the peak positions at 41.8°, 46.6°, 43.6°, 45.2° and 52.7° correspond to the (231), (141), (112), (240) and (132) crystal planes of tetragonal Ni3P, respectively. The peak positions at 40.66° and 47.3° correspond to the (111) and (200) planes of face-centered cubic Ru. From the XRD results, it can be seen that the nanoparticles are composed of mixed phases of phosphide Ni2P and Ni3P and precious metal Ru.

[0150] TEM showed the existence of two nanoparticles of different sizes. Particles with a diameter of about 10 nm were shown to be phosphides by elemental scanning, and particles with a diameter of about 3.5 nm were shown to be precious metal ruthenium by elemental scanning, indicating that under this condition, phosphides and precious metal ruthenium grow independently and cannot form a core-shell structure.

[0151] Comparative Example 6

[0152] (1) 0.1 mmol of nickel chloride was added to 15 mL of dodecylamine, and then 1.2 mL of tri-n-octylphosphine was added.

[0153] (2) The mixed solution obtained in step 1 was ultrasonically dispersed for 30 minutes, then transferred to a three-necked flask and heated with a heater. The temperature was first raised to 100°C and maintained for 15 minutes, and then raised to 300°C and maintained for 3 hours. The whole process was stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon was used for protection during the reaction.

[0154] (3) 0.01 mmol of ruthenium chloride was added to 15 mL of octadecene solution, and 3 mL of oleylamine was added at the same time, followed by heating at 150° C. for 30 min. The whole process was stirred with a magnetic stirrer at a stirring rate of 1000 rpm.

[0155] (4) The mixed solution obtained in step 3 is directly added to the solution in step 2. The temperature is first raised to 130° C. and heated for 30 min, and then the temperature is raised to 280° C. and maintained for 2 h. The whole process is stirred with a magnetic stirrer at a stirring rate of 1500 rpm, and high-purity argon is used for protection during the reaction.

[0156] (5) After the reaction was completed, the temperature was lowered to room temperature, and then washed with 30 mL of n-hexane and 10 mL of ethanol, and finally 10 mg of activated carbon was added for loading.

[0157] First, the crystal structure was characterized by X-ray diffractometer (XRD). In the obtained X-ray diffraction pattern, the peak positions at 40.8°, 44.6°, 47.3°, 54.2° and 54.9° correspond to the (111), (201), (210), (300) and (211) crystal planes of hexagonal Ni2P, respectively. From the XRD results, it can be seen that the nanoparticles are composed of mixed phase phosphides Ni2P and Ni3P. The peak position at 40.66° corresponds to the (111) plane of face-centered cubic Ru. From the XRD results, it can be seen that the nanoparticles are composed of phosphide Ni2P and precious metal Ru.

[0158] TEM showed the existence of two nanoparticles of different sizes. Particles with a diameter of about 10 nm were shown to be phosphides by elemental scanning, and particles with a diameter of about 5 nm were shown to be precious metal ruthenium by elemental scanning, indicating that under this condition, phosphides and precious metal ruthenium grow independently and cannot form a core-shell structure.

[0159] The core-shell nanoparticles prepared in Examples 1-6 were tested for oxygen evolution performance in acidic water electrolysis, and the test conditions were as follows:

[0160] (1) The test instrument is an electrochemical workstation, which adopts a three-electrode system. The working electrode is a rotating disk electrode, the counter electrode is a platinum sheet, and the reference electrode is an Ag / AgCl electrode.

[0161] (2) The electrolyte was 0.5 M H2SO4, and the linear voltammetry program was selected with a scan rate of 5 mV / s, a voltage range of -0.8 V to 1.7 V, and the scan was repeated 10 times.

[0162] The test results are shown in Table 2:

[0163] Table 2

[0164] sample <![CDATA[Overpotential (mV @ 10 mA / cm 2 )]]> Example 1 245 Example 2 234 Example 3 256 Example 4 268 Example 5 258 Example 6 273

[0165] It can be seen from Table 2 that the prepared Ru@Ni2P-Ni3P core-shell nanoparticles have a relatively low overpotential in acidic oxygen evolution. Combined with the Ru content in Table 1, it is revealed that the Ru@Ni2P-Ni3P core-shell nanoparticles prepared by the present invention have a low content of precious metal Ru, which can greatly reduce the cost of the PEM electrolyzer. On the other hand, due to the electronic interaction between the precious metal Ru shell and the Ni2P-Ni3P core, the Ru@Ni2P-Ni3P core-shell nanoparticles have excellent water electrolysis performance.

[0166] Table 3 shows the changes in the membrane electrode preparation process parameters of Examples 7-10 when the PEM electrolyzer is at 1A / cm 2 The cell voltage at 200 s is 2 mg / cm. It can be seen that when the Ru@Ni2P-Ni3P core-shell nanoparticle loading is 2 mg / cm 2When the hot pressing temperature is 120℃ and the hot pressing pressure is 3MPa, the small chamber electrolyzer voltage is the lowest and the performance is the best.

[0167] Table 3

[0168] sample <![CDATA[Cell voltage (V@1A / cm 2 )]]> Example 7 1.68 Example 8 1.67 Example 9 1.70 Example 10 1.69

[0169] Figure 1 It can be seen that the Ru@Ni2P-Ni3P core-shell nanoparticles as PEM anode catalysts have a cell voltage of 1.68V@1A / cm in the PEM electrolyzer. 2 , it can show a lower cell voltage when the content of precious metal Ru is very low, indicating that the above catalyst has great application potential.

[0170] like Figure 2 As shown, the long-term stability test found that after 20 hours of testing, the cell pressure basically did not decay, indicating that the catalyst is relatively stable.

Claims

1. A method for preparing a Ru@Ni2P-Ni3P core-shell structure catalyst, characterized in that: The following steps are involved: (1) adding a nickel precursor to a first solvent, then adding a phosphorus source, mixing, and heating, first raising the temperature to a first temperature and maintaining it for a certain time, and then raising the temperature to a second temperature and maintaining it for a certain time, and the reaction process is carried out under a protective atmosphere; (2) adding a ruthenium precursor to the second solvent and simultaneously adding a third solvent, heating and stirring to dissolve the ruthenium precursor; (3) adding the mixed solution obtained in step (1) to the solution in step (2), first raising the temperature to the third temperature and maintaining it for a certain time, and then raising the temperature to the fourth temperature and maintaining it for a certain time, and the reaction process is carried out under a protective atmosphere; (4) After the reaction is completed, the mixture is cleaned and loaded with a carrier.

2. The method for preparing the Ru@Ni2P-Ni3P core-shell structure PEM anode catalyst according to claim 1, characterized in that: The second temperature range in step (1) is 280-320° C., and the heating time is 30-200 min; the fourth temperature range in step (3) is 260-320° C., and the heating time is 10-300 min.

3. The method for preparing the Ru@Ni2P-Ni3P core-shell structure PEM anode catalyst according to claim 1, characterized in that: The first temperature range in step (1) is 10-150° C., and the heating time is 1-30 min; the third temperature range in step (3) is 10-150° C., and the heating time is 1-30 min.

4. The method for preparing the Ru@Ni2P-Ni3P core-shell structure PEM anode catalyst according to claim 1, characterized in that: The molar ratio of the ruthenium precursor to the nickel precursor is 1:1-1:

15.

5. The method for preparing the Ru@Ni2P-Ni3P core-shell structure PEM anode catalyst according to claim 1, characterized in that: The volume ratio of the second solvent to the third solvent is 8:1-1:

1.

6. The method for preparing the Ru@Ni2P-Ni3P core-shell structure PEM anode catalyst according to claim 1, characterized in that: The nickel precursor includes at least one of nickel chloride, nickel acetate, nickel sulfate, and nickel acetylacetonate; the ruthenium precursor includes at least one of ruthenium acetylacetonate, ruthenium chloride, ruthenium acetate, bis(pentamethylcyclopentene)ruthenium, and bis(pentamethylcyclopentene)ruthenium.

7. The method for preparing the Ru@Ni2P-Ni3P core-shell structure PEM anode catalyst according to claim 1, characterized in that: The first solvent in step (1) includes at least one of oleylamine, dodecylamine, octadecylamine, and trivinylamine; the second solvent in step (2) includes at least one of n-hexane, cyclohexane, octadecene, oleic acid, p-phenylene ether, and dimethyl sulfoxide; the third solvent in step (2) includes at least one of oleylamine, dodecylamine, octadecylamine, and trivinylamine.

8. A PEM membrane electrode, characterized in that: The catalyst in the PEM membrane electrode is a Ru@Ni2P-Ni3P core-shell structure catalyst prepared by the method described in claim 1.

9. The PEM membrane electrode according to claim 8, characterized in that: The loading of the Ru@Ni2P-Ni3P core-shell catalyst is 1-4 mg / cm 2 .

10. A method for preparing a PEM membrane electrode according to claim 8, characterized in that: The proton exchange membrane, the catalyst layer and the gas diffusion layer are formed by hot pressing; the temperature during hot pressing is 10-150° C. and the pressure is 1-5 MPa.